A comparative study of the mechanical properties of a construction tool handle - Kozioł, Stanisław; Samborski, Tomasz; Zbrowski, Andrzej (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The article presents a method and the results of a comparative study related to the mechanical properties of a construction manual tool handle, namely, the mason trowel. The study was conducted on behalf of Comensal, a tool manufacturer, and it was a part of the process to improve and modernize the construction and manufacturing technology of the product. In the study, strength tests were conducted for three different constructions of the handles, which were made of different materials, and for the connections between the handles and the working plate of the tool. The results of the study and the manufacturer’s information on the production cost and manufacturing conditions became the basis in the decision making process to implement the most advantageous solution and to purchase appropriate manufacturing equipment. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)